Persepsi Pengguna Bus Trans Koetardja Terhadap Fasilitas Bagi Kaum Difabel - Effendy, Amalia; Nazaruddin, Nazaruddin; Meliyana, Meliyana (Jurnal Teknik Sipil Unaya, 2024)
To attract public interest in using Bus Trans Koetaradja , the operator must be able to provide and provide adequate facilities and provide good service to the people who use the Bus. Good service is a factor that will encourage people to use the bus as a  daily transport. People with disabilities are vulnerable people including pregnant women, elderly people and people with disabilities, because of their limitations they are entitled to special facilities in the use of public facilities and infrastructure, including buses. This research was conducted to examine the level of satisfaction of Bus Transkoetaradja users towards facilities for people with disabilities. The research was conducted by survey, Researcher distributing questionnaires to 100 Trans Koetardja Corridor I Bus Users. The results showed that the overall level of satisfaction of Trans Koetaradja Bus users for the availability of facilities and infrastructure for people with disabilities received a satisfactory score, but there are criteria that are considered quite satisfied, such as the comfort of the ramp at the bus stop, this is definitely a concern for the company to further improve bus services.